Pengaruh Strategi Accelerated Learning Terhadap Hasil Belajar Siswa PAI Madrasah Aliyah - Hartati, Herni (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
Many students feel that PAI learning is less interesting and boring because it is associated with a lot of theory and memorization. The Accelerated Learning Strategy makes the learning atmosphere more fun so that it can motivate students to learn. This study aims to see the effect of Accelerated Learning Strategy on student learning outcomes. This research is a quasi-experimental research using Two Group Pretest – Posttest Design which involves two classes that are given different treatments. This research was conducted at Madrasah Aliyah (MA) Al-Imam Abi Yazid Al-Basthomiy Dumai for the Academic Year 2022/2023. The population of this study were all students of class X Odd Semester MA Al-Imam Abi Yazid Al-Basthomiy. The research sample was determined by using the Cluster Random Sampling technique so that class X 3 was obtained as an experimental class taught with Accelerated Learning Strategy and class X 1 as a control class taught by conventional learning in which each class consisted of 43 people. The independent variable in this study is the Accelerated Learning Strategy while the dependent variable is student learning outcomes. The instrument used in this study was a student learning outcome test which was given as a pretest and posttest. The data were normally distributed and the sample came from a homogeneous population, so the t-test was used. The results of data analysis showed that there was an effect of Accelerated Learning Strategy on student learning outcomes.